The Non-Return of Azerbaijani Students Educated Abroad under State Sponsorship - Hasanova, Aydan; Maharramova, Tahira; Hasanova, Nazakat (ADA University, 2025)
This capstone examines why a substantial share of Azerbaijani students sponsored by the State Program choose not to return home after completing their studies abroad. Through semi-structured focus-group interviews with nine non-returning alumni and expert interviews with three program administrators, the study explores economic drivers (wage disparities, pension mismatches, remote-work opportunities), higher-education barriers (faculty shortages, misaligned degree quotas, limited research infrastructure), and sociocultural frictions (management-style clashes, weak contractual safeguards, prestigecentered program design). Three policy bundles are developed: (1) binding return clauses with graduated-repayment options; (2) indexed stipends, return bonuses, and matchinggrant schemes; and (3) a reintegration infrastructure comprising a Returnee Coordination Unit, fellowships, alumni networks, and institutional reforms in academia and the public sector. Evaluated for efficacy, feasibility, and cost, these options reveal that no single measure suffices. Instead, a blended approach—combining a flexible service requirement, strategic financial incentives, comprehensive reintegration supports, and workplace modernizations—offers the best path to reverse brain drain and foster sustainable “brain gain.” An adaptive governance framework is proposed to monitor outcomes and iteratively refine program design.
Keywords: Scholarships and fellowships -- Government policy -- Azerbaijan; Education, Higher -- Government policy -- Azerbaijan; Student mobility -- Economic aspects.; Public administration -- Personnel management -- Azerbaijan.; Brain drain -- Azerbaijan.; Educational planning -- Economic aspects -- Azerbaijan; Public and International Affairs